A Comparison of Single-Stage and Two-Stage Dry-Hopping Regimes. (2nd October 2019) - Hauser, Dean G.; Simaeys, Karli R. Van; Lafontaine, Scott R.; Shellhammer, Thomas H.
Abstract: Multi-stage dry-hopping is a technique that is widely used by brewers to achieve intense hop aroma in beer. However, a thorough analysis of its efficacy does not exist in the published literature. The goal of this study was to compare the properties of beers produced by single or two-stage dry-hopping at the same cumulative rate. On the pilot scale (80–100 L), an un-hopped base beer was subjected alternately to single- or two-stage dry-hop additions at 386, 772, and 1544 g/hL using Centennial hops. Separately commercial beers (∼350 hL batch size) were dry-hopped at 733 g/hL in single or two-stage additions using a combination of Amarillo, Simcoe, Cascade, Citra, and CTZ pellets. Pilot scale dry-hopped beers showed increases in residual extract, pH, bitterness units, humulinones, and total polyphenols, accompanied by a decrease in iso-α-acids with increasing hop dose. Changes in bitterness units, humulinones, and iso-α-acids all appeared to be more pronounced in the two-stage dry-hopped beers. In contrast, commercial beers were nearly identical in terms of chemical composition. Significant increases in six aroma attributes scaled by a trained panel were observed as a result of two-stage dry-hopping in the pilot scale treatments. Slight increases in aroma potential were observed for the commercial beer made with two-stage additions, although these differences were not statistically significant. These results illustrate the impact multi-stage dry-hop additions have on beer aroma, and provide direction to brewers to consider whether multi-stage dry-hopping may yield desirable results while potentially using less hop material.